ALBANIAN BANKRUPTCY LAW, WHERE WE STAND, WHERE TO GO - Valbona Ballkoci; Najada Senja (European Scientific Journal, ESJ, 2015)
The number of businesses in our country going bankrupt is growing. Businesses that start the procedures of insolvency are increasing, but only few of them are intended to be called legally bankrupt. This is due to the fact that the Albanian bankruptcy law has some shortage that pre vents proper legal regulation of bankrupt businesses. Bankruptcy laws have evolved over time in response to changing economic conditions and the political and economic strength of different interest groups. The Albanian bankruptcy law has been under scrutiny in recent times. The aim of this article is to give an overview of German insolvency law, where we find the German principles under which the law in force is based, and USA insolvency law, in order to highlight the aspect in which the Albanian law requires adjustments.